Tracking Interoperability Service in Digital Libraries for Orthodox Art and Knowledge - Goynov, Maxim; Rangochev, Konstantin; Paneva-Marinova, Desislava; Sapunjiev, Vladimir (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
The implementation of the idea of improved access and effective usage of digital libraries content has led to a new type of services, providing their wider content integration and merging. In this context, the analysis of integrating service usability is essential and gives new directions for functionality extension and improvement. This paper presents an analysis of the usage of the interoperability service, compiling content from two digital libraries for Orthodox art and knowledge – the Encyclopaedia Slavica Sanctorum and the Bulgarian Iconographical Digital Library.